1999
DOI: 10.1897/1551-5028(1999)018<2123:eonlfi>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Northern Leopard Frogs in the Green Bay Ecosystem to Polychlorinated Biphenyls, Polychlorinated Dibenzo-P-Dioxins, and Polychlorinated Dibenzofurans Is Measured by Direct Chemistry but Not Hepatic Ethoxyresorufin-O-Deethylase Activity

Abstract: We measured concentrations of polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs), and polychlorinated dibenzofurans (PCDFs) in northern leopard frogs collected from the Green Bay ecosystem and explored the catalytic activity of hepatic cytochrome P450-associated monooxygenase (P450 enzyme) as a biomarker for exposure to aryl hydrocarbon receptor (AhR) agonists. The two hypotheses tested were PCH concentrations in northern leopard frogs would be positively correlated with sediment polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…2), it was clear that PCDD/PCDF concentrations in frogs clearly reflected the concentration levels in their habitats. These findings confirm those reported by Huang et al [15].…”
Section: Resultssupporting
confidence: 93%
“…2), it was clear that PCDD/PCDF concentrations in frogs clearly reflected the concentration levels in their habitats. These findings confirm those reported by Huang et al [15].…”
Section: Resultssupporting
confidence: 93%
“…For this and past studies [7], we used sediment PCB and heavy‐metal concentrations, which are associated [1], as an index to the relative level of contamination at the sites. In 1994 and 1995, we collected sediment samples (depth, top 5 cm) from around the edge of the enclosures that we installed at the field sites, although sediment PCB data were from other sources for sites C1 and C3 [2] and site R1 (K.A.…”
Section: Methodsmentioning
confidence: 99%
“…Body burdens of PCBs, their possible relation to sediment contamination, and the sensitivity of amphibians to these compounds in the field are relatively unknown and are not easily predicted or approximated [6]. Two studies [7,8] found that levels of PCBs in adult leopard frogs ( Rana pipiens ) and green frogs ( Rana clamitans melanota ) were positively correlated with levels in sediments ( n = 5 sites each). We have extended these studies by performing PCB congener‐specific analyses on tadpoles and metamorphosed frogs raised at many sites and on the embryo batches from which they were derived.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a reported association between intersex and polychlorinated dibenzofurans in A. crepitans in Illinois over 15 years ago (Reeder et al ., ) and the associations between industrial contaminants and intersex detailed above (Reeder et al ., ; Skelly et al ., ), evidence for endocrine disruption in wild anurans for non‐pesticidal pollutants is scarce. Contaminants, including BPA, PCBs and phthalates are present in anuran environments (Oehlmann, Oetken & Schulte‐Oehlmann, ), and some have been detected in anuran tissue (Huang et al ., ; Karasov et al ., ). Furthermore, there are indications that PCB levels found in anuran tissue may affect reproductive endpoints (Jofre & Karasov, ).…”
Section: Field Studies On Wild Amphibian Populationsmentioning
confidence: 98%